Sensitivity of Terminalia catappa L. Toward Aeromonas hydrophila - Purba, Andre Manusun; Riauwaty, Morina; Syawal, Henni (Jurnal Perikanan dan Kelautan, 2020)
Terminalia catappa is commonly present in tropical area and its can be used for increasing pH in fish culture and it also be used as disinfectant. The aimed of this study was to obtain a dose of T. catappa leaf solution which was able to inhibit the growth of Aeromonas hydrophila. This research was conducted from April to August 2019, at the Laboratory of Parasites and Fish Diseases, Department of Aquaculture, Faculty of Fisheries and Marine, Riau University. The method used in this study is an experimental method, namely disk diffusion KIRBY-BAUER to see the sensitivity of T. catappa leaf solution against A. hydrophila. The Kirby-Bauer method uses a 6 mm diameter blank disk, to reduce the level of error, then it is repeated three times. The treatments applied were K: Control (Oxytetracycline) at a dose of 30 µg / disk, P1: Giving T. catappa leaf solution 100% dose, P2 (90%), P3 (80%), P4 (70%), P5 (60%) , P6 (50%), P7 (40%), P8 (30%), P9 (20%), P10 (10%) P11 (9%), P12 (8%), P13 (7%), P14 (6%), P15 (5%), P16 (4%), P17 (3%), P18 (2%), P19 (1%). The results showed that the T. catappa leaf solution was able to inhibit the growth of A. hydrophila bacteria at doses of 100-2% with inhibitory zone diameters of 13.9-6.5 mm.